Being Gay, Being Christian You can be both. - Edser, Stuart (Wollombi : Exisle Pub., 2012)
The primary aim of this book is to explain to gay or same-sex attracted people that they can be both gay and Christian - that the two are not mutually exclusive. Author Stuart Edser threads his own extraordinary story throughout the text, using this and his experience as a clinician to guide his thinking. At the end, he presents an alternative model of Christian discourse to that which we usually hear and offers a positive voice often absent from the Church's utterances on homosexuality.
Cover; Title Page; Copyright Page; Dedication; Contents; Foreword; Preface; Why Another Book?; Two Kinds of Knowledge; Being Gay or Lesbian Today; Important Background Research; The Biology of Being Gay; The Psychology of Being Gay; Coming Out; Sound People, Sick Therapy; The Bible and Christianity; The Evangelical View of Homosexuality; The Catholic View of Homosexuality; Final Thoughts; Notes; Index; Index of Biblical References.
Description based on print version record.
Keywords: Bible and homosexuality; Christian life; Homosexuality -- Religious aspects -- Christianity; Religion; RELIGION / Christian Theology / Ethics; Electronic books